An Antibody Recognizing the Apical Domain of Human Transferrin Receptor 1 Efficiently Inhibits the Entry of All New World Hemorrhagic Fever Arenaviruses - Helguera, Gustavo Fernando (2012)
Five New World (NW) arenaviruses cause human hemorrhagic fevers. Four of these arenaviruses are known to enter cells bybinding human transferrin receptor 1 (hTfR1). Here we show that the fifth arenavirus, Chapare virus, similarly uses hTfR1. Wealso identify an anti-hTfR1 antibody, ch128.1, which efficiently inhibits entry mediated by the glycoproteins of all five viruses, aswell as replication of infectious Junín virus. Our data indicate that allNWhemorrhagic fever arenaviruses utilize a commonhTfR1 apical-domain epitope and suggest that therapeutic agents targeting this epitope, including ch128.1 itself, can be broadlyeffective in treating South American hemorrhagic fevers.